Language policy and multilingual practices in the family (Siddhajyoti Interdisciplinary Journal, 2020)
This paper discusses on how language policy, language ideologies, parental language planning and children’s role in the shaping of family language practices are associated in the multilingual practice context. The objective of this study was to explore the language policies focus on heritage language maintenance by negotiating and instantiating in parents-children interactions and contribution of children’s language practices to shape the family multilingualism in the process of socialization. I have used qualitative research design to collect the data in this study. Three participants from different language background were selected. The research participants were interviewed using a semi-structured interview technique to collect the data. The study concluded that family members’ contribution to the shaping of family language practices and policies in daily life interactions is the most important and language ideologies play a vital role in language policy and language acquisition in the family of multilingual practice.